Sex-specific differences in the relationship between fasting plasma glucose and carotid plaque in a cardiovascular high-risk population: a cross-sectional study - Xu, Mengjie; Xu, Kai; Lin, Weiguo; Sun, Ruixue; Yan, Shaorong; Chen, Xiaoshu; Lin, Yuzhan (Frontiers in Endocrinology, 2025)
BackgroundDespite extensive research on the epidemiological risk factors linking diabetes and carotid plaques, evidence regarding sex-specific differences remains scarce. This study aims to investigate the gender differences in the association between fasting blood glucose levels and the risk of carotid plaques among cardiovascular high-risk populations.MethodsThis study used cross-sectional data from a large prospective cohort study. From 2019 to 2020, fasting blood glucose and carotid ultrasound examinations were conducted on high-risk cardiovascular populations in the pilot area. The independent variable was fasting blood glucose, and the dependent variable was the presence or absence of carotid plaques. A multivariable logistic regression model was used to calculate risk ratios. Generalized additive models combined with curve fitting were employed to assess the nonlinear relationship between fasting blood glucose levels and carotid plaques in the overall population and different genders.ResultsThis study included 1,063 cardiovascular high-risk patients. In the fully adjusted model, fasting blood glucose levels in men were positively associated with carotid plaques (OR = 1.21, 95% CI: 1.02-1.45, p = 0.0312). In women, fasting blood glucose levels were also positively associated with the risk of carotid plaque formation (OR = 1.15, 95% CI: 0.95-1.39). The generalized additive model results showed a linear relationship between fasting blood glucose levels and carotid plaques in the overall population. Stratified results indicated a linear relationship in men, while a nonlinear relationship was observed in women.ConclusionThere is an association between fasting blood glucose levels and carotid plaque, with an increased risk of carotid plaque as fasting blood glucose rises. Moreover, this relationship differs between sexes.